A Case for Change in Adult Critical Care Training for Physicians in the United States: A White Paper Developed by the Critical Care as a Specialty Task Force of the Society of Critical Care Medicine*. Issue 10 (October 2018) - Tisherman, Samuel A.; Spevetz, Antoinette; Blosser, Sandralee A.; Brown, Daniel; Chang, Cherylee; Efron, Philip A.; O'Connor, Michael; Sevransky, Jonathan E.; Wessman, Brian T.
Abstract : Objectives: In the United States, physician training in Critical Care Medicine has developed as a subspecialty of different primary boards, despite significant commonality in knowledge and skills. The Society of Critical Care Medicine appointed a multidisciplinary Task Force to examine alternative approaches for future training. Design: The Task Force reviewed the literature and conducted informal discussions with key stakeholders. Specific topics reviewed included the history of critical care training, commonalities among subspecialties, developments since a similar review in 2004, international experience, quality patient care, and financial and workforce issues. Main Results: The Task Force believes that options for future training include establishment of a 1) primary specialty of critical care; 2) unified fellowship and certification process; or 3) unified certification process with separate fellowship programs within the current specialties versus 4) maintaining multiple specialty-based fellowship programs and certification processes. Conclusions: 1) Changing the current Critical Care Medicine training paradigms may benefit trainees and patient care. 2) Multiple pathways into critical care training for all interested trainees are desirable for meeting future intensivist workforce demands. 3) The current subspecialties within separate boards are not "distinct and well-defined field[s] of medical practice" per the American Board of Medical Specialties. Recommendations for first steps are as follows: 1) as the society representing multidisciplinary critical care, the Society of Critical Care Medicine has an opportunity to organize a meeting of all stakeholders to discuss the issues regarding Critical Care Medicine training and consider cooperative approaches for the future. 2) A common Critical Care Medicine examination, possibly with a small percentage of base-specialty–specific questions, should be considered. 3) Institutions with multiple Critical Care Medicine fellowship programs should consider developing joint, multidisciplinary training curricula. 4) The boards that offer Critical Care Medicine examinations, along with national critical care societies, should consider ways to shorten training time. Abstract : Supplemental Digital Content is available in the text.